Kajian produksi dan pendapatan nelayan tangkap rajungan (portunus pelagicus linnaeus, 1758) di Kelurahan Lampopala Sulawesi Tenggara pada saat covid-19 - Nurfadilah; La Ola, La Onu; Piliana, Wa Ode (Universitas Halu Oleo, 2022)
The determinants of the income of crab fishermen are production results and prices. The purpose of this study was to examine how much the income changes of crab fishing fishermen in Lampopala Village, Rumbia District, Bombana Regency, Southeast Sulawesi during the Covid-19 pandemic which was carried out in January 2021. Respondents in this study were determined through themethod, cluster random sampling namely selecting fishermen who using traps and nets with a sample size of 10 trap fishermen and 10 net fishermen. Furthermore, themethod was census applied to all respondents by interview to obtain primary data on capture fishermen, namely name, age, education, business experience, amount of fuel, catch, fishing time, cost, and bait based on a structured questionnaire. The data obtained is then calculated using the formula for total costs, revenues, and revenues. The fishing process carried out by fishermen with traps and nets is the same, namely the preparation of fishing gear, including engines, boats, fuel, consumption, and bait as well as the selection oflocations fishing ground. The income of bubu fishermen is an average of Rp.4,030,449/month during Covid-19. Meanwhile, the average income of net fishermen is Rp. 3,183,813/month during Covid-19. The production of trap fishermen during Covid-19 remained at 180 kg/month but with increased profits to Rp. 5,429,652. On the other hand, the production of net fishermen has decreased to 120 kg/month with a profit of Rp. 3,204,766 during Covid-19. The thing that causes a decrease in the profits of fishermen catching nets is the reduced amount of production caused by constraints such as torn nets and restrictions on activities by the government. The crab fishermen have increased the selling price of the crab which was originally between Rp.30,000 before Covid-19 to Rp.35,000 during Covid-19. Most of the crabs are sold to companies/collectors so that they can increase the income of crab fishermen.